Learning application of kangguru method as treatment in weight low storage baby at home - Girsang, Bina Melvia; Ritonga, Fajar Utama; Sinulingga, Samerdanta (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Mothers who take care of the kangaroo method feel more confident in caring for their babies compared to mothers who do not take care of the kangaroo method. Kangaroo care methods also increase the closeness of the mother with her baby (bonding attachment), reduce feelings of stress to the mother as well as to the baby, and make the mother and baby more calm and relaxed. Mother's confidence will improve along with the increase in the ability of mothers to care for their babies. Based on information about the Purba Horison Village, the main problems and alternative solutions were found, namely the lack of means in terms of electronic communication more or less to make the community lack of knowledge in terms of health that also affects family parenting patterns and living standards of the local community. For this reason, counseling and training in the health sector are needed to increase community knowledge that can improve the quality of life of the Purba Horison village community.